Performance of Military Personnel at the TNI AL IV Batam Main Base: Adaptability Analysis, and Superior Support - M. Sarip Kodar; Muhamad Adam; Agustina Hanafi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Military personnel performance is a crucial factor in achieving operational effectiveness, especially at the TNI AL IV Batam Main Base. Although adaptability and dual positions have been shown to have a significant effect on personnel performance, there is a knowledge gap regarding how superior support can moderate the relationship. This study aims to analyze the effect of adaptability on personnel performance, with superior support as a moderating variable, which is a new aspect and has not been widely studied in the military context. A quantitative approach was used in this study, using the Structural Equation Modeling (SEM) method through AMOS software. Data were obtained from 30 respondents who were military personnel at the TNI AL IV Batam Main Base. The results showed that adaptability and dual positions had a positive and significant effect on personnel performance. In addition, superior support was shown to moderate the relationship between adaptability and dual positions with performance, strengthening the influence of both factors. The model used in this study also showed good fit, so it can be relied on to explain the relationship between variables. These findings fill the gap in previous research and emphasize the importance of developing adaptability, effective dual-job management, and superior support in order to improve the performance of military personnel in a dynamic and challenging work environment